SDGs IN ISLAMIC COMMERCIAL AND SOCIAL FINANCE LITERATURE: A BIBLIOMETRIC AND CONTENT ANALYSIS - Mohammad Zen Nasrudin Fajri; Abdul Latif; Muhammad Afif Haidar Fajlurrahman; Adamu Abubakar Muhammad (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
A number of Muslim-majority countries scored low in SDGs achievements, mainly due to the limitation of funding sources. Many Islamic scholars propose Islamic Finance to address this issue. This research was performed to determine the impactful authors, institutions, countries, journals and keywords in the literature on SDGs in Islamic Commercial Finance (ICF) and Islamic Social Finance (ISF). Furthermore, this paper also presents the discussion on relevant trends and proposes directions for future research in this field. A bibliometric approach and content analysis were administered in analyzing 139 articles retrieved from the Scopus database. The results show that Hassan R. is the most productive author, while Universitas Airlangga and Malaysia are leading institution and country focus in this research theme. “International Journal of Ethics and System” is the leading journal, and the most influential keywords are “SDGs”, “Islamic finance”, and “waqf”. Six research streams were identified: 1) Governance and Performance for SDGs; 2) Innovation for Financing SDGs; 3) Digitalization for SDGs Realization; 4) Green Investment for SDGs Realization; 5) Solution for Socioeconomic Issues; and 6) Contribution to Economic Sustainability. Governments and regulators are recommended to strengthen Islamic finance by ensuring Shariah compliance, promoting blended finance, regulating fintech, incentivizing green sukuk, standardizing SDG reporting, and fostering cross-border harmonization to enhance sustainability, financial inclusion, and economic growth while balancing innovation and risk management.